U.S. monetary policy spillovers to emerging markets: Both shocks and vulnerabilities matter - Shaghil Ahmed; Ozge Akinci; Albert Queralto (Federal Reserve Bank of New York, 2021)
We explore how the sources of shocks driving interest rates, country vulnerabilities, and central bank communications affect the spillovers of U.S. monetary policy changes to emerging market economies (EMEs). We utilize a two-country New Keynesian model with financial frictions and partly dollarized balance sheets, as well as poorly anchored inflation expectations reflecting imperfect monetary policy credibility in vulnerable EMEs. Contrary to other recent studies that also emphasize the sources of shocks, our approach allows the quantification of effects on real macroeconomic variables as well, in addition to financial spillovers. Moreover, we model the most relevant vulnerabilities structurally. We show that higher U.S. interest rates arising from stronger U.S. aggregate demand generate modestly positive spillovers to economic activity in EMEs with stronger fundamentals but can be adverse for vulnerable EMEs. In contrast, U.S. monetary tightening's driven by a more-hawkish policy stance cause a substantial slowdown in activity in all EMEs. Our model also captures the challenging policy tradeoffs that EME central banks face, and we show that these tradeoffs can potentially be improved by clearer communications from them.
Keywords: E32; E44; F41; 330; financial frictions; U.S. monetary policy spillovers; adaptive expectations